Establishment of neutron dose calibration fields based on a ²⁵²Cf source by Monte-Carlo method - Hoang , Van Nguyen; Ho , Huu Thang; Tran , Ngoc Toan; Nguyen , Xuan Hai (Nuclear Science and Technology, 2016)
This paper presents calculation results based on Monte-Carlo method to select an appropriate neutron moderator and design four configurations for a 252Cf irradiation system. These configurations provide six neutron spectra with the various average energies (1.04 MeV, 1.38 MeV, 1.69 MeV, 2.05 MeV, 2.46 MeV and 2.93 MeV) suitable for the calibration of neutron survey meters and personal dosimeters.